Cognitive style and on-line database search experience as predictors of Web search performance - Palmquist, Ruth A.; Kim, Kyung-Sun (Journal of the American Society for Information Science, 2000)
This study sought to investigate the effects of cognitive style (field dependent and field independent) and on‐line database search experience (novice and experienced) on the World Wide Web (WWW) search performance of undergraduate college students (n = 48). It also attempted to find user factors that could be used to predict search efficiency. Search performance, the dependent variable, was defined in two ways: (1) time required for retrieving a relevant information item, and (2) the number of nodes traversed for retrieving a relevant information item. The search tasks required were carried out on a University Web site, and included a factual task and a topical search task of interest to the participant. Results indicated that while cognitive style (FD/FI) significantly influenced the search performance of novice searchers, the influence was greatly reduced in those searchers who had on‐line database search experience. Based on the findings, suggestions for possible changes to the design of the current Web interface and to user training programs are provided.